The Role of Learning Media in Learning Mathematics: a Systematic Literature Review - Muhaimin, Lukman Hakim; Juandi, Dadang (Journal of Mathematics and Mathematics Education, 2023)
Learning media is a tool that can assist the process of transferring knowledge from teacher to student so that learning is more effective. This literature study provides a comprehensive study of the benefits and role of instructional media in learning mathematics. This literature systematics uses Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) as a research approach. The PRISMA stages include: identification, screening, eligibility, and include. Acquisition of 113 articles sourced from Scopus, ERIC, and Proquest databases taken in the last decade. Through PRISMA, 12 review articles were obtained, which became data to answer research questions. The results showed that Indonesia has the most research areas, 9 out of 12 studies. SMA level has the most application of instructional media from the research collected. Various types of media are used, and these various types of media result in the development of various mathematical materials through learning media. Some of the material developed includes geometry (in seven studies), trigonometry (in two studies), as well as material on functions, algebra, and quadratic equations (each in one study). Learning media can also develop mathematical cognitive abilities, including mathematical problem-solving, mathematical understanding, mathematical communication, critical mathematical thinking, mathematical representation, mathematical reasoning, and spatial abilities. In addition, affective abilities can also be developed, such as learning independence (in two studies), self-confidence, creativity, and learning concentration.